2015
DOI: 10.1007/s12263-015-0490-2
|View full text |Cite|
|
Sign up to set email alerts
|

Fasting enriches liver triacylglycerol with n-3 polyunsaturated fatty acids: implications for understanding the adipose–liver axis in serum docosahexaenoic acid regulation

Abstract: We investigated the effect of short-term fasting on coordinate changes in the fatty acid composition of adipose triacylglycerol (TAG), serum non-esterified fatty acids (NEFA), liver TAG, and serum TAG and phospholipids in mice fed ad libitum or fasted for 16 h overnight. In contrast to previous reports under conditions of maximal lipolysis, adipose tissue TAG was not preferentially depleted of n-3 PUFA or any specific fatty acids, nor were there any striking changes in the serum NEFA composition. Short-term fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
(68 reference statements)
5
13
0
Order By: Relevance
“…Among these changes, the largest effect was a 92-fold up-regulation of Agpat2, which is consistent with prior reports of a role for this enzyme specifically in triacylglycerol storage [13,14]. These data are therefore consistent with reports that hepatic TAG synthesis is increased [15], and hepatic TAG stores are enriched following an acute fast [16][17][18][19], and that the liver acts as the main site of phospholipid synthesis in the fasted state [20].…”
Section: Resultssupporting
confidence: 91%
“…Among these changes, the largest effect was a 92-fold up-regulation of Agpat2, which is consistent with prior reports of a role for this enzyme specifically in triacylglycerol storage [13,14]. These data are therefore consistent with reports that hepatic TAG synthesis is increased [15], and hepatic TAG stores are enriched following an acute fast [16][17][18][19], and that the liver acts as the main site of phospholipid synthesis in the fasted state [20].…”
Section: Resultssupporting
confidence: 91%
“…These differences are unlikely to reflect the FA composition of the diets, which delivered similar proportions of PUFA sand MUFA in HFD formulas and a greater proportion of PUFA in CD. After overnight fasting, HLC increased in the CD group, as expected [17][18][19]. This hepatic lipid deposition was accompanied by modifications of the unsaturation indices similar to those induced by an HFD (i.e., increase of PUFA and reduction of MUFA indices).…”
Section: Discussionsupporting
confidence: 61%
“…In addition, an early association between HFD feeding and hepatic insulin resistance has been reported [8,9,16]. Increased hepatic FA influx leading to lipid accumulation is also observed with prolonged fasting, on mobilization of adipose stores [17][18][19], but in this case hepatic insulin resistance is not present [18]. Thus, alterations in the hepatic lipid pool are a physiological response to increased circulating FA levels, and are not necessarily associated with changes in insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that fasting and impaired glucose regulation can increase hepatic content of triacylglycerol and eventually result in the accumulation of lipid in the liver parenchyma (Lonardo et al 2015, Marks et al 2015. In the present experiment, tissue sections of rats revealed clear vacuoles, representing stored lipid droplets by starvation and also during refeeding.…”
Section: Discussionsupporting
confidence: 57%